Against Modernization: The Existence of Traditional Islamic Boarding Schools in North Padang Lawas District - Dalimunthe, Rasyid Anwar; Asari, Hasan; Nurmawati, Nurmawati (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research was conducted with the aim of providing a clear picture of the philosophical and sociological basis for the existence of traditional pesantren in the midst of modernization, so that it can be illustrated with strong reasons to remain with the traditional pesantren. The method chosen in this study is a qualitative method. In terms of approach, this research utilizes a field research descriptiveThe action taken by the researcher was to go to the 'field' to make observations about Against Modernization: The Existence of Traditional Islamic Boarding Schools in North Padang Lawas Regency. The findings in this study. First, the philosophical basis for the existence of traditional pesantren in the midst of modernization is the advice of the clergy, parents and because the kyai wishes to produce cadres of scholars, the great glory of teaching knowledge, and the wish to preserve the understanding of ahlussunnah wal jama'ah. The first two sociological foundations are that the pesantren still receives assistance and enthusiasm from the community, such as assistance with dormitories, classrooms, the Koran, and sending their children to these traditional pesantren. Second, because many alumni have succeeded, such as teachers, lecturers, DPR, DPRD and DPRI. The three traditional Islamic boarding schools in North Padang Lawas Regency still receive support from both the regional and central governments such as BOS funds, classrooms, multilevel dormitories and several other things. From this, the researcher concludes that traditional Islamic boarding schools will still be able to survive as they are typical in this modern era, if the traditional Islamic boarding school clerics have the right guidelines in developing their traditional Islamic boarding schools. So that the good aim is to prove to the public its ability to produce quality generations and be able to compete can be trusted by the wider community.